Orbital angular momentum transmission based on satellite formation relay in space communications - Zhao, Yufei (2023)
Orbital Angular Momentum (OAM) transmission is expected to be implemented for large capacity communication. However, the conical beam and the coaxial all-phase reception brings painful difficulties. As a promising solution to overcome this difficulty, an OAM multiplexing transmission method is proposed for use in a satellite formation relay scheme in this paper. Specifically, the channel model of the OAM wave from the base station to the relay satellites and then forwarded by relays to the central receiver is established and analyzed. In order to explore the feasibility of the scheme and its influencing factors, we analyze the influence of orbit distribution and random jitter on channel capacity based on the orbit parameters of actual satellite formations. The simulation results show that the uniform and evenly spaced satellite formation has the highest multiplexed channel capacity and anti-interference performance.